THE INFLUENCE OF DIGITAL COMMUNICATION STRATEGY AND SERVICE QUALITY ON PATIENT LOYALTY AT RSU PINDAD BANDUNG - Wendi Yuliawan; Vira Putri Febriyani; Neng Aat Solihat (Jurnal Penelitian Progresif, 2026)
This study aims to analyze the influence of Digital Communication Strategy and Service Quality on Patient Loyalty at RSU Pindad Bandung. The background of this research lies in the importance of implementing effective communication strategies and improving service quality to build patient trust and loyalty in the digital era. The research method employed is associative with a survey approach involving 200 patient respondents. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression, validity and reliability tests, classical assumption tests, t-test, F-test, and coefficient of determination (R²). The results show that partially, the Digital Communication Strategy has an effect of 24.90%, while Service Quality has an effect of 56.90% on Patient Loyalty. Simultaneously, both variables have a significant influence on Patient Loyalty by 81.8%, while the remaining 18.2% is affected by other factors beyond this study. These findings emphasize that effective digital communication management and high-quality service are key factors in enhancing patient loyalty and strengthening the hospital’s positive image.